Low-temperature phosphorescence of dicyanoacetylene in rare gas solids - Turowski, Michał; Crépin, Claudine; Couturier-Tamburelli, Isabelle; Piétri, Nathalie; Kołos, Robert (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
A strong visible ã3∑u+ – X̃1∑g+ luminescence was observed upon the UV excitation of cryogenic rare gas (argon,krypton, and xenon) matrices doped with dicyanoacetylene (NC4N). Spectra and lifetimes of this phosphorescence have been measured. A detailed analysis of resolved vibronic bands is presented.